Memahami Kepuasan Pelanggan : Mengeksplorasi Customer Experience dengan Pendekatan Observasi Online - Antonius Felix; Lia, Singgi, Katherine , Sarah Felina , Cindy Claudia Natalie (STIE Amkop Makassar, 2024)
The restaurant industry is one of the most popular businesses among the public due to its high profit potential. The purpose of this research is to determine the extent to which customer experiences, including product quality, pricing, and service quality, influence customer satisfaction. This study adopts a qualitative approach with descriptive and expnatory methods based on secondary data. Data collection involves two samples from online platforms, Tripadvisor and Google Review, to gather information about customer perceptions of the Lobo & Juno restaurant. The results of this study indicate that customers perceive satisfaction from the quality of products, especially the service provided, and although the prices are relatively high, the excellent service quality compensates for the cost.